2019
DOI: 10.4000/techne.1791
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the colours of Hermogenes’ temple of Artemis: architectural surface analysis in the Antikensammlung Berlin

Abstract: I. Des monuments colorés : la polychromie architecturaleRésumé. Le temple d'Artémis à Magnésie du Méandre, dans l'actuelle Turquie occidentale, est un jalon de l'architecture hellénistique. Nous savons que son créateur, Hermogène de Priène, était déjà salué dans l'Antiquité pour ses innovations. Malgré notre bonne connaissance de l'architecture même du temple, nous n'avions aucune information sur les applications de couleur. Un travail de recherche conduit en équipe dans la Collection des antiquités de Berlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…[4] . These findings are in agreement with the known architectural polychromy of the temple of Athena at Priene and of Apollo at Didyma and the Mausoleum at Belevi [11] . Unfortunately, we didn't find the presence of other pigments such as yellow ochre, green ochre or azurite, which could give a deeper idea of the used pigments as well as on the decoration.…”
Section: Considerationssupporting
confidence: 91%
See 2 more Smart Citations
“…[4] . These findings are in agreement with the known architectural polychromy of the temple of Athena at Priene and of Apollo at Didyma and the Mausoleum at Belevi [11] . Unfortunately, we didn't find the presence of other pigments such as yellow ochre, green ochre or azurite, which could give a deeper idea of the used pigments as well as on the decoration.…”
Section: Considerationssupporting
confidence: 91%
“…Several authors demonstrated the presence of traces of pigments in the Parthenon sculptures, on Campana reliefs from the Palatine Hill and Colosseum Valley in Rome and on the Frieze of the Siphnian Treasury [7][8][9][10] . Zink et al, showed the colours of Hermogenes' temple of Artemis [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation